External and Internal Quality of the Quail Eggs Fed Ration with Different Level of Metabolizable Energy and Protein - Sudrajat, Deden; Wahyuni, Dewi; Nur, Hanafi; Kardaya, Dede (Universitas Halu Oleo, 2022)
Quail eggs are a source of animal protein that the public can consume. In addition to the low price, eggs also contain nutrients needed by the body. So it is necessary to pay attention to the quality of the eggs before consuming them. Egg quality that can be assessed is derived from internal and external quality. The quality of the eggs is influenced by various factors, including the content of the ratio given, especially the energy-protein balance of the feed. This study aimed to assess the external and internal quality of quail eggs with different protein and energy levels. The research was carried out for 42 days in the poultry house of the Animal Husbandry Study Program, Faculty of Agriculture, Djuanda University. The feed ingredients formulated in this study as the basic ration were yellow corn, fine bran, soybean meal, fish meal, premix, DCP, CaCO3, CPO, and Cr-O. The design used was a completely randomized design (CRD) with four treatments and four replications with six quails per cage unit. The research data were analyzed by analysis of variance (ANOVA) if the data showed significantly different results (P<0.05), followed by Duncan's test. The variables observed in this study were egg weight, shell weight, percentage of eggshell weight, eggshell thickness, egg index, egg white weight, egg yolk weight, egg white weight percentage, egg yolk weight percentage, Haugh unit (HU). The results showed that the balance of energy and protein differences were not significantly different in all variables. Based on the research results, it can be concluded that the quail ration with the balance of protein 17% and metabolizable energy 2800 kcal/kg has been able to maintain the internal and external quality of eggs in quail and produce standard egg quality.Keywords: protein energi balance; egg white, yolk, haugh unit